Kedudukan Hukum Perjanjian Hak Asuh Anak yang Dibuat oleh Notaris - Mutiara Febriana; Kadek Cahya Susila Wibawa (Syntax Corporation, 2023)
Research on the Legal Position of Child Care Agreement made by a notary aims to find out how the role of the notary in making child custody agreements, as well as to find out the legal position of the child custody agreement made by the notary. This research is a study with a normative juridical approach, namely examining the principles of law, legal rules, and legal systematic by examining library materials to obtain secondary data.The results showed that the notary as a public official who had the authority to make a deed. Agreement on parenting rights agreed by both parties (husband and wife) ratified by the notary is a notary deed that has legal force and is an authentic deed. In the case of husband and wife, divorce before court hearing, The notary deed is very instrumental, especially for judges, namely accelerating judges in leading the trial process and making it easier to make decisions. The position of the child due to divorce, among others, is both the father or mother still obliged to maintain and educate his children solely based on the interests of the child, the judge has the authority to give a decision, the father must be responsible for all the education costs needed by the child, However, if in reality the father can not be sufficient or fulfill these obligations, then the judge can decide that the mother joins him and the court can order that the interests of Sianak are guaranteed after their parents are divorced, because it is placed under the responsibility of his parents, where They are still required to maintain and educate the child until the child is an adult. If in its implementation there is one party to define the contents of the agreement contained in the notary deed, other parties who are disadvantaged can make a lawsuit to the District Court.